Field and Contestation of Religious Identity: Christian Responses to the Rise of Islamism in Post-Reformation Indonesia - Tedi Kholiludin; Ubbadul Adzkiya' (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2023)
This study explores the response of Christianity, particularly among protestant leaders, to Islamism in Indonesia during the post-reform period. It uses a qualitative approach, using in-depth interviews and literary materials. The research uses grounded theory to understand how the public sphere serves as a platform for expressing conflicts over religious identities. The results show that Christianity perceives Islamism as a political division, triggering reactions and requiring strategies to establish boundaries and reinforce identities. Feedback from Christianity includes seeking state commitment, forming alliances with moderate groups, engaging in internal introspection, fostering national duty, and establishing daily institutions. The study suggests that Christianity’s response to Islamism is a contestation within the cultural production arena, where both groups assert dominance through their distinct modalities. There is no unified Christian response to the growing spirit of Islamism, with demographics, memories, and experience as a social institution determining response variations.